Stability of class II correction with the Austro Repositioner associated with multi-brackets fixed appliances in dolichofacial patients - María Dolores Austro-Martinez; Ana I. Nicolás-Silvente; Mª Angeles Requena; Marta Carazo-Austro; José Antonio Alarcón (BMC, 2024)
Abstract Background The purposes of the present study were to evaluate the changes produced by the Austro Repositioner, and to assess the stability of Class II malocclusion treatment with the Austro Repositioner associated with fixed appliances and its capacity to control the vertical dimension in dolichofacial patients. Methods A group of patients with Class II malocclusion due to mandibular retrognathism and a dolichofacial growth pattern treated with the Austro Repositioner combined with fixed appliances were compared to a matched untreated control group of subjects with Class II malocclusion. Evaluations were made on the basis of lateral cephalograms taken at T1 (initial records), T2 (end of treatment), and T3 (1 year after treatment). Statistical comparisons were performed with paired- and two-sample t tests. Results The experimental (treated) group comprised 30 patients, 14 boys and 16 girls, and the control group comprised 30 subjects (15 boys and 15 girls) with similar ages at T1, T2 and T3. In the treated group, a significant decrease in the ANB angle was found (− 3.79 ± 1.46; p < 0.001). No significant differences were found in the maxillary skeletal measurements. In contrast, the SNB angle showed a significant increase of 3.77 ± 1.49 in the treated group compared with a nonsignificant increase of 0.77 ± 1.55 in the control group (p = 0.002). Vertical changes showed a significant decrease in the FMA angle (− 3.36 ± 1.62), while the lower anterior facial height distance and the overbite increased significantly in the treated group, reflecting a change in vertical dimensions after treatment. No significant changes were observed in either the treated or control group during the one-year posttreatment period; thus, the treatment results remained stable. Conclusions The Austro Repositioner combined with fixed appliances could be considered an optimal treatment modality in Class II dolichofacial patients.